2023
DOI: 10.3390/plants12091865
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Development of Polymorphic Microsatellite Markers and Genetic Diversity Analysis for the Halophyte Suaeda aralocaspica (Amaranthaceae)

Abstract: Suaeda aralocaspica, which is an annual halophyte, grows in saline deserts in Central Asia with potential use in saline soil reclamation and salt tolerance breeding. Studying its genetic diversity is critical for effective conservation and breeding programs. In this study, we aimed to develop a set of polymorphic microsatellite markers to analyze the genetic diversity of S. aralocaspica. We identified 177,805 SSRs from the S. aralocaspica genome, with an average length of 19.49 bp, which were present at a dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…Likewise, halophytes also show a wide range of photosynthetic pathways ranging from C 3 , through C 4 to CAM [36]. Halophytes also exhibit genetic diversity within and between species [73][74][75]. Furthermore, genetic studies have revealed variations in genes associated with salt tolerance mechanisms, such as ion transporters and osmolyte synthesis enzymes [32,34,76].…”
Section: Biological Diversity Of Halophytesmentioning
confidence: 99%
“…Likewise, halophytes also show a wide range of photosynthetic pathways ranging from C 3 , through C 4 to CAM [36]. Halophytes also exhibit genetic diversity within and between species [73][74][75]. Furthermore, genetic studies have revealed variations in genes associated with salt tolerance mechanisms, such as ion transporters and osmolyte synthesis enzymes [32,34,76].…”
Section: Biological Diversity Of Halophytesmentioning
confidence: 99%